Vacuum-Assisted Continuous Circular Capsulorhexis Using Bimanual Irrigation and Aspiration System of Phaco Machine in Immature Cataract - Huseyin Oksuz; Mutlu C. Daglioglu; Mesut Coskun; Özgür İlhan; Esra Ayhan Tuzcu; Nilufer Ilhan; Emre Ayıntap; Uğurcan Keskin; İbrahim Taşkın (Journal of Ophthalmology)
Seventy-eight eye of 65 patients were enrolled in this retrospective clinical study. Two-side ports are made with a 23-gauge stiletto knife. The irrigation handpiece is introduced into the anterior chamber through one side port and 27-gauge cystotome is introduced through the other one. Anterior capsular flap is created with cystotome. The capsular flap is vacuumed with a 25-gauge visco elastic’s cannula, which connected to the phaco machine vacuum. The continuous circular capsulorhexis (CCC) is completed with the using bimanual irrigation and aspiration system of phaco machine. Vacuum-assisted CCC technique was used in 78 cases of uncomplicated immature senile cataracts. All cases were done under sub-Tenon’s anesthesia. A complete CCC was achieved in all cases. Performing CCC with our technique is easy, safe, and cheap. It may be an alternative method to CCC by using OVD and forceps.